- #1

- 2

- 0

## Homework Statement

I would like to derive the equation Vc=Vss+(Vi-Vss)*e^(-t/RC)

Vss is the steady state voltage

Vi is the initial capacitor voltage

Vc is the capacitor voltage

## The Attempt at a Solution

I tried to find solution using laplace transform. E=iR+1/c∫idt.

Taking laplace, E/s=I(s)R+1/(cs)*I(s)-q(0+)/(cs)

Put q(0+)=cVc(0+)=cVi

Then taking inverse laplace

i(t)=(E-vi)/R *e^(-t/RC)

Vc=1/c∫idt

=(E-vi)(1-e^(-t/RC))

What is wrong? why am i not getting the correct answer? Please help...